Active Components of Komak Beak Bongkor (Lablab purpureus (L.) Sweet) Seeds - Nur Indah Julisaniah; Baiq Aulia Dewi Agustin; Sukiman Sukiman; Kurniasih Sukenti (Jurnal Biologi Tropis, 2022)
Komak bean (Lablab purpureus (L.) Sweet) belongs to the family Fabaceae and subfamily Papilionidae. Komam bean is cultivated by people for consumption as an additional food source. Informationabout the active compound content of komak bean is needed as a reference in the utilization of komak. This research aims to determine the active compounds contained in komak seed (Lablab purpureus (L.) Sweet). This study used GC-MS analysis to determine the active components of the komak bean seed. Based on research result, komak Beak Bongkor bean contain 13 active components, they were toluenea, methyl octanoat, adacene 12, isododecane, caprylic acid, retardex, 1-undecene 7-methyl-, methyl caprate, capric acid, benzoic acid 4-ethyl-, palmitic aldehyde, methyl laurate dan lauric acid.